2011
DOI: 10.5123/s1679-49742011000100004
|View full text |Cite
|
Sign up to set email alerts
|

A percepção materna sobre vivência e aprendizado de cuidado de um bebê prematuro

Abstract: ResumoObjetivo: analisar a percepção materna sobre vivência e aprendizado de cuidado de um bebê prematuro. Metodologia: pesquisa qualitativa, com 21 mães atendidas no ambulatório de neonatologia de um hospital geral do SUS, em Fortaleza-CE. Os dados foram coletados por meio de entrevistas e formulário, submetidos a técnica de análise de conteúdo temática e estatística descritiva. Resultados: a vivência das mães é marcada pelo trauma do parto prematuro. Ocorrem conflitos e sofrimento, decorrentes da inexistênci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
25

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 13 publications
(18 reference statements)
1
7
0
25
Order By: Relevance
“…the situation that the parents face, as also described in other similar studies (18) . Mexican families invest an average of 50% of the family economic income in health care problems, which is a factor of social impoverishment.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…the situation that the parents face, as also described in other similar studies (18) . Mexican families invest an average of 50% of the family economic income in health care problems, which is a factor of social impoverishment.…”
Section: Resultssupporting
confidence: 66%
“…This aid includes payment for the neonate's hospitalization, although it does not cover everything for low-income families. There are other types of expenses, such as the trips to the municipal headquarters during hospitalization or the medical equipment needed to continue care for the baby in the home at the parents' own expense (6,(18)(19) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mães que realizam cuidados diários em seus bebês na UTIN aumentam sua interação com os filhos, fortalecendo o vínculo e tendo oportunidade de aprender e praticar o que lhe é ensinado sobre o cuidado ao bebê de risco. Com efeito, algumas mães superaram o medo e a insegurança de cuidar de seu bebê, com a confiança e a motivação no desempenho das atividades diárias, transmitidas por profissionais de saúde que incentivam a interação do binômio mãe-filho e ensinam às mães os cuidados básicos que elas deverão assumir após a alta hospitalar do filho (18) . E quando a mãe passa a assumir esses cuidados em casa, mesmo com dificuldades, ela demonstra o sentimento de ter o filho para si, sentindo-se "mais mãe" do que no ambiente hospitalar, quando o bebê parecia pertencer à equipe de saúde.…”
Section: Temática 2 Vínculo E Participação Das Mães No Cuidado Com Ounclassified
“…It should be noted that there may be other reasons why mothers are not taking the babies for consultations, according to a conducted study 31 , the mothers reported difficulties in leading their children to medical appointments, because they live in remote locations, spending on transport and leave early in their homes.…”
Section: Something Like That … It's Complicate To Talk About It (Lamentioning
confidence: 99%